An Integrated Approach for Renewable Energy Resource and Plant Location Selection - Nuriyev, Mahammad (International Journal of Energy Economics and Policy, 2021)
Renewable energy resources ranking, and power plant location selection are multi-criteria decision-making (MCDM) problems. These problems can be solved as two-phase decision-making tasks separately and sequentially or, in a unified form, as a single-step task. In this paper, we are studying the efficiency and applicability of the unified approach based on fuzzy and Z-information, and TOPSIS technique. Alternatives for the single-step approach are generated based on renewables available in the country and potential geographical locations for these resources. Considering the importance of weights in MCDM and the multiplicity of approaches to criteria weighting, subjective, objective, AHP-based, and combination of the subjective and objective weights are used for decision matrix weighting. Comparative analysis of the solutions, based on various weights, allows making a reliable solution. The results of the study and problem solution confirm the efficiency and applicability of the combined approach. The advantage of the unified single step solution is that this approach, in addition to the solution of the main task, provides to decision-maker additional information about preferable next best renewable and location option as well. Keywords: renewables selection, multi-criteria decision, fuzzy and Z-information, plant location selection, criteria weights. JEL Classifications: D81, P48, Q35, Q42 DOI: https://doi.org/10.32479/ijeep.10880